Peroneal perforator pedicle propeller flap for lower leg soft tissue defect reconstruction: Clinical applications and treatment of venous congestion. (June 2017) - Shen, Lifeng; Liu, Yiyang; Zhang, Chun; Guo, Qiaofeng; Huang, Wenhua; Wong, Kelvin Kian Loong; Chang, Shimin
Objective: To describe the characteristics of the perforator vessel in the peroneal artery of the lower leg and to explore the use of perforator pedicle propeller flaps to repair soft tissue defects in the lower leg, heel and foot. Methods: This retrospective study enrolled patients with soft tissue defects of the distal lower leg, heel and foot who underwent surgery using peroneal perforator-based propeller flaps. The peroneal artery perforators were identified preoperatively by colour duplex Doppler ultrasound. The flap was designed based on the preoperatively-identified perforator location, with the posterior border of the fibula employed as an axis, and the perforator vessel as the pivot point of rotation. Patients were followed-up to determine the outcomes. Results: The study analysed 36 patients (mean age, 39.7 years). The majority of the soft tissue defects were on the heel (20; 55.6%). The donor-site of the flap was closed in 11 patients by direct suturing and skin grafting was undertaken in 25 patients. Postoperative complications included venous congestion (nine patients), which was managed with delayed wound coverage and bleeding therapy. All wounds were eventually cured and the flaps were cosmetically acceptable. Conclusions: The peroneal perforator pedicle propeller flap is an appropriate choice to repair soft tissue defects of the distal limbs.